Applied Research on APIA Scientific Skin Management Methodology: Enhancing Skin Health Through Personalized Approaches - Wang W; Gao W; Kuang X; Yi F (Clinical, Cosmetic and Investigational Dermatology)
Wei Wang,1,* Wenhong Gao,1,* Xinjue Kuang,2,3 Fan Yi2,3 1Revacl (Shanghai) Biotechnology Co., Ltd., Shanghai, People’s Republic of China; 2Key Laboratory of Cosmetic, China National Light Industry, Beijing Technology and Business University, Beijing, People’s Republic of China; 3Institute of Cosmetic Regulatory Science, Beijing Technology and Business University, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Fan Yi, Beijing Key Laboratory of Plant Resources Research and Development, Beijing Technology and Business University, No. 11, Fucheng Road, Haidian District, Beijing, 100048, People’s Republic of China, Tel +86 15652701818, Email fantasyee@btbu.edu.cnBackground: Common cosmetic skin concerns including dryness, acne, pigmentation, sensitivity, and ageing significantly impact quality of life. Traditional skincare methods often rely on generic strategies, overlooking the complexity and individual differences in skin problems. The APIA (Assessment, Program, Implementation, Accompany) skin management system is a proven, scientific and systematic skin health management programme that prioritizes personalized assessment and long-term tracking. APIA consists of four parts: Assessment (skin identification and analysis), Program (development of a skin management programme), Implementation (programme implementation), and Accompany (ongoing care).Purpose: This study aimed to explore and validate the application of the APIA methodology in skin management practice and its impact on skin health to offer new insights and practical recommendations for skin management practices.Methods: This study employed a before-and-after comparative study design to evaluate the skin of 74 participants who were treated with the APIA methodology. The effectiveness of the APIA methodology was assessed by comparing skin metrics before and after its implementation. The assessment criteria included cosmetic and functional skin indicators, such as stratum corneum thickness, radiance, and sebum production.Results: After implementing the APIA methodology, participants exhibited significant improvements in multiple skin indicators, including stratum corneum thickness, gloss, sebum secretion, pore blockage, capillary dilation, colour, softness, smoothness, elasticity, and temperature (p < 0.05). Additionally, improvements in self-perception, skin condition, acne, pigmentation, sensitivity, ageing, and skin around the eyes were statistically significant. There was no significant difference in pore size before and after management (p > 0.05).Conclusion: The APIA skin management methodology is effective at improving skin health and offers a scientific, systematic, and sustainable solution for skin care. This method can effectively address common skin problems and maintain the healthy state of the skin. It also has potential applications in the fields of cosmetology and skin health management.Keywords: scientific view of beauty, skin management, skin health improvement, behavioural interventions, skin managers, skin care products (cosmetics), Apia skin management system